Comparative transcriptomics of 3 high-altitude passerine birds and their low-altitude relatives - Hao, Yan (Proc Natl Acad Sci U S A, 2019)
High-altitude environments present strong stresses for living organisms, which have driven striking phenotypic and genetic adaptations. While previous studies have revealed multiple genetic adaptations in high-altitude species, how evolutionary history (i.e., phylogenetic background) contributes to similarity in genetic adaptations to high-altitude environments is largely unknown, in particular in a group of birds. We explored this in 3 high-altitude passerine birds from the Qinghai-Tibet Plateau and their low-altitude relatives in lowland eastern China. We generated transcriptomic data for 5 tissues across these species and compared sequence changes and expression shifts between high- and low-altitude pairs. Sequence comparison revealed that similarity in all 3 high-altitude species was high for genes under positive selection (218 genes) but low in amino acid substitutions (only 4 genes sharing identical amino acid substitutions). Expression profiles for all genes identified a tissue-specific expression pattern (i.e., all species clustered by tissue). By contrast, an altitude-related pattern was observed in genes differentially expressed between all 3 species pairs and genes associated with altitude, suggesting that the high-altitude environment may drive similar expression shifts in the 3 high-altitude species. Gene expression level, gene connectivity, and the interactions of these 2 factors with altitude were correlated with evolutionary rates. Our results provide evidence for how gene sequence changes and expression shifts work in a concerted way in a group of high-altitude birds, leading to similar evolution routes in response to high-altitude environmental stresses.